SEXUALITY EDUCATION TO PREVENT INTIMATE PARTNER VIOLENCE - Malažinskienė, Jolanta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The “discovery” of intimate partner violence in the 1970s by the feminist movement, which considered it to be a private affair between two people, showed that the phenomenon is a recurrent one, occurring in a wide range of romantic relationships, whether committed, dating, or casual, and both current and former, across races, social classes, ages, adults and adolescents. Research has shown that existing criminal justice, health and social interventions do not address intimate partner violence. Changing culturally constructed attitudes that make men dominant and controlling, women dependent and invisible, and the use of gender-sensitive policies are key to addressing violence against women. It is argued that comprehensive sexuality education, as a preventive measure that introduces an appreciation of personal needs in terms of the well-being of the other person and of society, can help to address intimate partner violence. The aim of this article is to show the importance of a sexuality education perspective in the prevention of intimate partner violence against women. The study shows that in order to prevent intimate partner violence against women and girls, it is important to develop the ability to recognise violence related to unequal power in relationships, to be able to name types of violence, and to be able to identify symptoms of violent behaviour. The research design used was qualitative research, semi-structured interviews to collect data, and the participants were women who had experienced violence in intimate relationships.